Neonatal duodenal obstruction due to a preduodenal portal vein associated with intestinal malrotation: A case report - Hamouda, Hechmi Ben; Salem, Radhia Hadj; Rabeh, Hatem; Amor, Ilhem Ben; Belhassen, Samia; Soua, Hahib; Nouri, Abdellatif; Rhouma, Khaled Ben; Hamza, Hassine; Mahjoub, Bahri; Sfar, Mohamed Tahar (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Preduodenal portal vein (PDPV) is a rare congenital vascular anomaly in which the portal vein passes unusually anterior to the duodenum rather than posteriorly. Generally asymptomatic, PDPV may rarely cause duodenal obstruction in newborn. We report a full term 16-day-old girl who presented with recurrent non-bilious vomiting soon after birth. Clinically, she was dehydrated and the abdomen was not distended. Abdominal radiography showed a dilated stomach and the first part of duodenum with some gas in the distal intestines. Abdominal ultrasound revealed distended stomach, dilatation of proximal duodenum and intestinal malrotation. Upper gastrointestinal contrast study showed severe gastroesophageal reflux with delayed passage of contrast to the small bowel, distended stomach and proximal duodenum confirming partial duodenal obstruction. Surgical exploration revealed a portal vein crossing over the duodenum anteriorly and intestinal malrotation. A duodenoduodenostomy was performed and Ladd's procedure was added to correct the intestinal malrotation. The post-operative course was uneventful and 6 months after the operation the patient is in good condition with normal development and no intestinal problems